Facebook engagement in Malaysian Ministry 2024 - Muhamad Zaki Mustafa; Muhammad Raqib Mohd Sofian; Safiyyah Ahmad Sabri; Mohd Yahya Mohamed Ariffin; Mohd Faizal Kasmani (Universitas Ahmad Dahlan, 2026)
Non-Indexed Publication